Status Gizi, Status Kesehatan dan Gaya Hidup pada Wanita Lakto Vegetarian dan Non Vegetarian - Widya Astuti; Hadi Riyadi; Faisal Anwar; Ni Ketut Sutiari (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Vegetarian diet is one of the lifestyle changes. The aims of this study was to analyse the differences of nutritionalstatus, health status, and lifesytle and to analyse correlation between nutritonal status, health status, withlifestyle in lakto vegetarian groups and non lakto vegetarian groups. The design of this study was cross-sectionalstudy include 80 women aged 40-65 years old and was conducted in Bali Province. Data were analyzed using ManWhitney U Test and difference test and Rank Spearman relationship test. This research was funded by Neys-vanHoogstraten Foundation, the Netherlands. The measurement of characteristic of subjek and lifestyle used questioner.The measuerment of body weight used digital scales. Body height was measurement used staturemater,blood pressure was measurement used sphygmomanometer and Hb levels used cyanmethemoglobin. Nonvegetariangroup had higher proportion of obesity and hypertension (50%; 37,5%) than lacto vegetarian groups. Lactovegetarian groups had higher anemia status than non vegetarian groups. The result show there were significantdifferences between nutritional status and consumption coffee into two groups (p<0,05). There were show nocorrelation between nutritonal status, health status, with lifestyle (p>0.05). This study indicates lacto vegetariangroup had better nutritional status, health status, and lifestyle than non-vegetarian group. Lacto-vegetarian grouphad higher risk of anemia.